Modeling and Control Design of an Autonomous Hybrid Wind/Energy Storage Generation Unit - A. Abdalla, Shiref; Mansor, Hasmah; F. Hasbullah, Nurul; M. Kassem, Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the present paper is to investigate a controller design and simulations of an autonomous hybrid wind turbine system with a variable-speed permanent magnet synchronous generator (PMSG) and a system for storing energy. The proposed system is mainly composed of a wind turbine-driven permanent magnet synchronous generator, an uncontrolled rectifier, a DC/DC converter, a DC/AC inverter, and static loads. Furthermore, the mathematical model of the studied sub-systems and two control loops are considered. The first one is the controller, which needed to preserve the DC-link voltage fixed at its desired value. The second one is the controller, which needed to regulate the charge/discharge modes of the storage battery. The suggested hybrid wind/energy storage power generation model is considered and analyzed in the absence of a controller first. Then, the considered hybrid wind/energy storage power generation unit with the proposed controller is examined through a step change in wind speed. Digital simulation results show that the power desired by the linked loads may be successfully supplied and transported by the presented hybrid wind turbine and energy storage power generation system based on proportional-integral-derivative (PID) controller. Also, the emulation results show that there is good foretelling of the electrical variable waveforms and good achievement in the case of the presented controller emulated with the case of the controller without controller as maintaining the load voltage fixed at its reference values.